Formulasi food bar berbasis pangan lokal tinggi asam amino esensial untuk anak balita stunting - Darawati, Made; Yunianto, Andi Eka; Doloksaribu, Tetty Herta; Chandradewi, AASP. (AcTion: Aceh Nutrition Journal, 2021)
Local food can be used as an alternative to additional food for toddlers, namely food bars. The study was conducted in June-November 2017. The design of this research was experimental using a completely randomized design (CRD). The food bar formulation was mixed with 20g and 25g tuna, while 20g and 25g mackerel fish. Organoleptic test data were analyzed using ANOVA. Proximate analysis of food bars using the AOAC method. Food bars' essential amino acid content was carried out using LCMS and total microbial analysis using the ALT method. Food bar analysis selected from the test results by semi-trained panelists and consumer panelists is f4 with 25g tuna mixing with indicators of color (p= 0,000), aroma (p= 0,003), taste (p= 0,040), and texture (p= 0,167). Food bar in 100 grams contains: energy 470,77 kcal, 15,65% protein, 24,13% fat, 47,74% carbohydrates, 2.14% ash, and 10.33% water. The results of the total microbial test on the food bar showed a value of 4,5 x 102 cfu/g and an Aw value of 0,86. Food bar formula F4 is a formula selected by panellists that contain ten high essential amino acids